Γ-Butenolide and furanone derivatives from the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178. (May 2017) - Phainuphong, Patima; Rukachaisirikul, Vatcharin; Tadpetch, Kwanruthai; Sukpondma, Yaowapa; Saithong, Saowanit; Phongpaichit, Souwalak; Preedanon, Sita; Sakayaroj, Jariya
Abstract: Chromatographic separation of the broth extract of the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178 resulted in isolation of four γ -butenolide-furanone dimers, aspersclerotiorones A-D, a furanone derivative, aspersclerotiorone E, and two γ -butenolide derivatives, aspersclerotiorones F and G, together with six known compounds, penicillic acid, dihydropenicillic acid, 5, 6-dihydro-6-hydroxypenicillic acid, 6-methoxy-5, 6-dihydropenicillic acid, coculnol and (4 R, 5 R )-4, 5-dihydroxy-3-methoxy-5-methylcyclohex-2-en-1-one. Their structures were determined by spectroscopic evidence. For aspersclerotiorones A and B, the structures were confirmed by single-crystal X-ray diffraction crystallography. Penicillic acid displayed weak antibacterial activity against Staphylococcus aureus and Escherichia coli with equal MIC values of 128  μ g/mL, and it was noncytotoxic towards African green monkey kidney fibroblast cells. Graphical abstract: Seven γ -butenolide and furanone derivatives, aspersclerotiorones A-G (1 –7 ), together with six known compounds, were isolated from broth ethyl acetate of the soil fungus Aspergillus sclerotiorum PSU-RSPG178. Structures of compounds1 and2 were confirmed by X-ray crystallography. Highlights: Aspergillus sclerotiorum PSU-RSPG178, a soil-derived fungus, was investigated. Four γ -butenolide-furanones, one furanone and two γ -butenolides were isolated. Additionally, five known γ -butenolides including penicillic acid were obtained. Structures of two γ -butenolide-furanones were confirmed by X-ray crystallography. Penicillic acid with weak antimicrobial activity was non-cytotoxic to Vero cells.